Evaluate: 8[7 - 6(4 - 2)] =

Question

Asked 7/31/2013 9:09:50 AM

Updated 6/27/2014 3:42:58 PM

5 Answers/Comments

This conversation has been flagged as incorrect.

debnjerry|Points 49169|

stickman|Points 6262|

Expert answered|neildychauco|Points 100|

Question

Asked 7/31/2013 9:09:50 AM

Updated 6/27/2014 3:42:58 PM

5 Answers/Comments

This conversation has been flagged as incorrect.

Rating

3

8[7-6(4-2)]

8[7-6(4-2)]

=(8)(7)+(8)(-12)

=56-96

=-40

8[7-6(4-2)]

=(8)(7)+(8)(-12)

=56-96

=-40

Added 6/27/2014 2:07:19 AM

This answer has been confirmed as correct and helpful.

3

3{[7(x-2)+4][2(2-5)+6]}

=(3)[7(x-2)+4+(-4x+10)+(-6)]

=(3)(7(x-2))+(3)(4)+(3)(-4x+10)+(3)(-6)

=21x-42+12-12x+30-18

=9x 18

=(3)[7(x-2)+4+(-4x+10)+(-6)]

=(3)(7(x-2))+(3)(4)+(3)(-4x+10)+(3)(-6)

=21x-42+12-12x+30-18

=9x 18

Added 6/27/2014 2:09:30 AM

This answer has been flagged as incorrect.

Flagged by yeswey [6/27/2014 3:41:20 PM]

3

5x + 10 + 15y = 5 (x+3 y+2)

Added 6/27/2014 2:10:36 AM

This answer has been confirmed as correct and helpful.

3

3{[7(x - 2) + 4] - [2(2x - 5) + 6]}

= 3[(7x - 14 + 4) - (4x - 10 + 6)]

= 3[(7x - 10) - (4x - 4)]

= 3(7x - 10 - 4x + 4)

= 3(3x - 6)

= 9x - 18

= 3[(7x - 14 + 4) - (4x - 10 + 6)]

= 3[(7x - 10) - (4x - 4)]

= 3(7x - 10 - 4x + 4)

= 3(3x - 6)

= 9x - 18

Added 6/27/2014 3:41:14 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [6/27/2014 3:42:00 PM]

3

2(b + 5) = 2b + 10

Added 6/27/2014 3:42:58 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [6/27/2014 3:55:40 PM]

27,357,926

questions answered

There are no comments.